Survival of Naïve T Cells Requires the Expression of Let-7 miRNAs - Pobezinskaya, Elena L.; Wells, Alexandria C.; Angelou, Constance C.; Fagerberg, Eric; Aral, Esengul; Iverson, Elizabeth; Kimura, Motoko Y.; Pobezinsky, Leonid A. (Frontiers in Immunology, 2019)
Maintaining the diversity and constant numbers of naïve T cells throughout the organism’s lifetime is necessary for efficient immune responses. Naïve T cell homeostasis, which consists of prolonged survival, occasional proliferation and enforcement of quiescence, is tightly regulated by multiple signaling pathways which are in turn controlled by various transcription factors. However, full understanding of the molecular mechanisms underlying the maintenance of the peripheral T cell pool has not been achieved. In the present study, we demonstrate that T cell-specific deficiency in let-7 miRNAs results in peripheral T cell lymphopenia resembling that of Dicer1 knockout mice. Deletion of let-7 leads to profound T cell apoptosis while overexpression prevents it. We further show that in the absence of let-7, T cells cannot sustain optimal levels of the pro-survival factor Bcl2 in spite of the intact IL-7 signaling, and re-expression of Bcl2 in let-7 deficient T cells completely rescues the survival defect. Thus, we have uncovered a novel let-7-dependent mechanism of post-transcriptional regulation of naïve T cell survival in vivo.